2012
DOI: 10.3892/mmr.2015.4456
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of miR-206-3p during mouse skin development is independent of keratinocyte differentiation

Abstract: MicroRNA-206 (miR-206), the homolog of which in mice is termed miR-206-3p, is a muscle-specific miRNA known to be important in the development of skeletal muscle, and is involved in smooth muscle innervation of the airway through the post‑transcriptional suppression of brain‑derived neurotrophic factor (Bdnf). miR‑206‑3p is also expressed at significant levels in adult and embryonic skin; however, its functional roles in adult skin and during skin development remain to be fully elucidated. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In this study, we demonstrated that miR-206-3p was significantly downregulated in shGATA4 OMSCs and their supernatant-derived exosomes. miR-206-3p is widely acknowledged as a characteristic, positive regulator of muscle differentiation 27 and is also expressed at remarkable levels in brown adipocytes 28 . Studies also indicated the potential role of miR-206-3p in the pathogenesis and pathology of osteoporosis 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that miR-206-3p was significantly downregulated in shGATA4 OMSCs and their supernatant-derived exosomes. miR-206-3p is widely acknowledged as a characteristic, positive regulator of muscle differentiation 27 and is also expressed at remarkable levels in brown adipocytes 28 . Studies also indicated the potential role of miR-206-3p in the pathogenesis and pathology of osteoporosis 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A list of microRNAs found to degrade BDNF mRNA transcripts in oncology research is as follows: miR-10a, miR-22, miR-204, miR-107, miR-382, miR-496, miR-497, miR-584, miR-744, miR-26a-1, and miR-26a-2 subtypes [24,28,58,60,72,75,78,88,93,94,96,102,112,125,126,128,132,133,137,190]. The evidence that miR-206 is able to suppress BDNF synthesis in diverse tissues such as the cardiac muscles, the skeletal muscles, and the endothelial tissue elucidates a role for microRNAs in tissue-tissue communication, although their actions might be locally regulated [30,43,45,48,61,92,102,115,120,139,142,169,171,177,191]. Some microRNAs are released from cells by membrane-derived vesicles, lipoproteins, and other ribonucleoprotein complexes and travel through the blood stream reaching recipient cells in distant tissues [192], providing communication between disparate cell types and diverse biological mechanisms and homeostatic pathways.…”
Section: Bdnf By Micrornasmentioning
confidence: 98%
“…Y. Peng et al, 2016;Xia et al, 2016;Xiang et al, 2016;Yan et al, 2015;Xiao yu Zhang et al, 2018). The evidences that miR-206 is able to suppress BDNF synthesis in diverse tissues such as the cardiac muscles, the skeletal muscles and the endothelial tissue elucidate a role for microRNAs in a tissue-tissue communication, although their actions might be locally regulated (Guan et al, 2021; S. T. Lee et al, 2012;Mu et al, 2015;Solomon et al, 2019;Tapocik et al, 2014;Tian et al, 2014;Xie et al, 2017;Xing et al, 2018;X. Yang et al, 2014;.…”
Section: Bdnf By Micrornasmentioning
confidence: 99%